HUBUNGAN ANTARA POLA ASUH ORANGTUA DENGAN PERILAKU HEDONISME DI KALANGAN SISWA SMA NEGERI 2 LEMBANG - Ageng saepudin kanda; Arum aji pramesti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Recently, people's lives have several lifestyles. Various lifestyles are chosen by individuals to spend time and do activities they enjoy. Besides that, the social environment increasingly supports the formation of an individual's lifestyle. One of the lifestyles that will be discussed in this research is the hedonic lifestyle. Determining each individual's lifestyle is based on the behavior and attitudes of the individual himself. Whether a decision taken by an individual is correct or not is based on the morals of each individual. Good morals will produce good decisions in life. The hedonic style arises from a feeling of wanting to duplicate what other people do to gain recognition from the social environment or as proof of the individual's social status. Other triggering factors that exist outside the individual are parents' parenting patterns towards children, the rapid flow of globalization faced by teenagers, peer interactions, and booming trends.